Economic Impact on Portfolio Selection: Risk and Correlation in Miscellaneous Financial Assets - Luna, Edwin Lizarazo; Rueda, Lina Rosenda Bonilla; Jaimes, Omar Hernán Nova; Rubio, Javier Leandro Chaparro (Journal of Posthumanism, 2025)
This study analyzes the economic consequences of portfolio selection decisions, emphasizing risk and correlation among a variety of financial assets. Employing quantitative analysis, the study applies portfolio optimization methods and adjusted risk measurements to underscore diversification prospects in global markets. The results suggest that adequate diversification significantly reduces systemic risk when compared with investing without taking it into account.